Emergency management of patients with Glanzmann thrombasthenia: consensus recommendations from the French reference center for inherited platelet disorders - Mathieu Fiore; Janine-Sophie Giraudet; Marie-Christine Alessi; Céline Falaise; Dominique Desprez; Roseline d’Oiron; Sophie Voisin; Marie-Françoise Hurtaud; Hélène Boutroux; Paul Saultier; Cécile Lavenu-Bombled; Gilles Bagou; et al. (Orphanet Journal of Rare Diseases, 2023)
Abstract Glanzmann thrombasthenia (GT) is a genetic bleeding disorder characterised by severely reduced/absent platelet aggregation in response to multiple physiological agonists. The severity of bleeding in GT varies markedly, as does the emergency situations and complications encountered in patients. A number of emergency situations may occur in the context of GT, including spontaneous or provoked bleeding, such as surgery or childbirth. While general management principles apply in each of these settings, specific considerations are essential for the management of GT to avoid escalating minor bleeding events. These recommendations have been developed from a literature review and consensus from experts of the French Network for Inherited Platelet Disorders, the French Society of Emergency Medicine, representatives of patients’ associations, and Orphanet to aid decision making and optimise clinical care by non-GT expert health professionals who encounter emergency situations in patients with GT.